Predictive Control Fed by An Indirect Converter With and Without Energy Storage Using PSO Optimization - Lammouchi, Zakaria; Barra, Kamel (Institute of Advanced Engineering and Science, 2015)
The paper presents an improved predictive direct control of a variable speed. The method is based on finite states space model of the converter. The proposed control method selects the optimal switching state of (Indirect Converter with and without energy storage for rectified and inverter) that minimizes the error between orthogonal torque, fluxs, and the reactive power components predictions to their computed values for all different voltage vectors. The optimal voltage vector that minimizes a cost function is then applied to the output of the power converter. The main aim of this paper is to propose an online optimization of the weighting factors by the Particle Swarm Optimization (PSO) approach well known by its robustness and fast convergence to the global optimum. Simulation results show that PSO strategy is very efficient to design accurately and quickly these weighting factors.